1997
DOI: 10.1007/s001289900529
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Dibenzo -p- Dioxins and Dibenzofurans in Lake Sediments from Chinese Schistosomiasis Areas

Abstract: Lake D is located in the south of China. The total area of the lake is about 3,000 km 2 . The dimension of the lakeland varies greatly with changing of seasons. It is an important source of grain and freshwater fish in China. However schistosomiasis japonica prevailed in this region for a long time, sodium pentachlorophenate(Na-PCP) has been sprayed since the 1960s to control the spreading of snailborne schistosomiasis. Being contaminants of technical Na-PCP, PCDD/Fs may enter the environment and contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…During the 1990s, the sediment in Dongting Lake was recognized to be highly contaminated with PCDD/Fs (Zheng et al, 1997). Total I-TEQ values of PCDD/Fs ranged from 130 to 891 pg g À1 with a mean value of 274 pg g À1 in the sediment samples collected in 1995.…”
Section: Declining Pcdd/f Levels In Sediments With Temporal Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the 1990s, the sediment in Dongting Lake was recognized to be highly contaminated with PCDD/Fs (Zheng et al, 1997). Total I-TEQ values of PCDD/Fs ranged from 130 to 891 pg g À1 with a mean value of 274 pg g À1 in the sediment samples collected in 1995.…”
Section: Declining Pcdd/f Levels In Sediments With Temporal Trendsmentioning
confidence: 99%
“…As one of the by-products of Na-PCP (Bao et al, 1995), PCDD/Fs may enter the environment and contribute to human exposure. The sediment in Dongting Lake was recognized to be highly contaminated with PCDD/Fs in 1995 (Zheng et al, 1997). Concerning the adverse effect of Na-PCP, Na-PCP has been prohibited spraying in this region since 1995.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, about 342 000 tons alkali was produced and the capacity of chloralkali production in Tianjin was the second largest in China (Song, 2000(Song, , 2001. Many studies have reported that PCP production may be a very important source of polychlorinated dibenzo-p-dioxin and dibenzofurans (PCDD/Fs) (Hagenmaier and Hermann, 1987;Rappe et al, 1991;Bao et al, 1995;Zheng et al, 1997;Xu et al, 2000). Endemic chloracne among the workers in a plant located in this chemical industry zone had been noted since 1974 (Cheng et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Multilayer silica column purification was commonly adopted, but the composition and structure of the column varied between different researchers (Luksemburg et al, 1996;Zheng et al, 1997;Wu et al, 2001a;Chen et al, 2003b;Hu et al, 2005). Water samples were enriched by XAD (Suplco Company), then freeze-dried and extracted by Soxhletapparatus (Wu et al, 2001b).…”
Section: Pcdd/f Samples Descriptionmentioning
confidence: 99%